Analysis of Environmental Protection and Management in the Perspective of Law Number 32 of 2009 - Kusnadi, Danang (JLASA (Journal of Law and State Administration), 2024)
Indonesia in recent decades has experienced a crisis regarding complex environmental problems that are interesting to study. Environmental protection and environmental management are very necessary for the sustainability of human life and the ecosystem in it. Efforts to protect and manage the environment are listed in Article 3 of Law Number 32 of 2009, namely: Protecting the territory of the Unitary State of the Republic of Indonesia from pollution and environmental damage. Ensuring human safety, health and life. Ensuring the survival of living things and the preservation of ecosystems is an increasingly urgent shared responsibility. Maintaining the preservation of environmental functions. Achieving harmony, harmony, and environmental balance. Ensuring the fulfillment of justice for current and future generations. Ensuring the fulfillment and protection of environmental rights as part of human rights. Manage the use of natural resources wisely. Realizing sustainable development. Anticipating global environmental problems. Efforts to plan, utilize, control, maintain, supervise and enforce the law. In Article 1 paragraph (2) of Law Number 32 of 2009, it is stipulated that environmental protection and management efforts consist of six important aspects: planning, utilization, control, maintenance, supervision, and law enforcement. The method used in this research is to use normative legal methods or also known as literature research, analyzing books, journals, and other documents.